2019
DOI: 10.1111/jne.12782
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection and immunomodulation of progesterone in the gut of a mouse model of Parkinson's disease

Abstract: Gastrointestinal symptoms appear in Parkinson's disease patients many years before motor symptoms, suggesting the implication of dopaminergic neurones of the gut myenteric plexus. Inflammation is also known to be increased in PD. We previously reported neuroprotection with progesterone in the brain of mice lesioned with 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP) and hypothesised that it also has neuroprotective and immunomodulatory activities in the gut. To test this hypothesis, we investigated proges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 76 publications
1
10
0
1
Order By: Relevance
“…Oestrogenic molecules also affects differentiation and myelination in oligodendrocytes [221] . Recent report also showed that even progesterone treatment in MPTP parkinsonian mouse model showed neuroprotective, anti-inflammatory and immune-modulatory effects, but whether the neuroprotective role begins in gut or brain is still unknown [222] .…”
Section: Gut Microbiota In Neuroprotectionmentioning
confidence: 99%
“…Oestrogenic molecules also affects differentiation and myelination in oligodendrocytes [221] . Recent report also showed that even progesterone treatment in MPTP parkinsonian mouse model showed neuroprotective, anti-inflammatory and immune-modulatory effects, but whether the neuroprotective role begins in gut or brain is still unknown [222] .…”
Section: Gut Microbiota In Neuroprotectionmentioning
confidence: 99%
“…In preclinical studies, estrogen has been shown to have antiapoptotic and antioxidant effects, 24 in addition to inhibiting α‐synuclein fibril stabilization and aggregation 25 . Several studies have demonstrated that higher total lifetime estrogen exposure may be associated with a decreased risk of PD in women, 26‐29 although some other studies have been inconclusive 24,30‐34 …”
Section: Gaps and Controversiesmentioning
confidence: 99%
“…25 Several studies have demonstrated that higher total lifetime estrogen exposure may be associated with a decreased risk of PD in women, [26][27][28][29] although some other studies have been inconclusive. 24,[30][31][32][33][34] The timing of estrogen exposure and association with sexual hormones may be critical factors 35 : it has been shown that postmenopausal estrogen-only treatment among women with hysterectomy may increase the risk of PD compared to no increased risk when women experience natural menopause and receive usual treatment with a combination of estrogen and progesterone. 36 A recent retrospective analysis showed that greater duration of HRT was associated with reduced risk of neurodegenerative disease, including PD.…”
Section: Sex Hormonesmentioning
confidence: 99%
“…These events could be related to the homeostatic and protective actions of steroids in neural cells, as well as to the manifestation of sex differences in neurodegenerative disorders . The involvement of progesterone in neuroprotection and immunomodulation in Parkinson's disease is described in a mouse model in the study by Jarras et al Other neuroactive steroids are involved in complications of sleep deprivation, in the imbalance of inhibitory and excitatory actions during pregnancy that program for poor behavioural outcomes in a sex‐dependent manner later in life, in some psychiatric diseases such as Tourette's syndrome, and in the regulation of mitochondrial function in tauopathies …”
mentioning
confidence: 99%